2020
DOI: 10.1126/sciadv.aax5692
|View full text |Cite
|
Sign up to set email alerts
|

Parallel PRC2/cPRC1 and vPRC1 pathways silence lineage-specific genes and maintain self-renewal in mouse embryonic stem cells

Abstract: The transcriptional repressors Polycomb repressive complex 1 (PRC1) and PRC2 are required to maintain cell fate during embryonic development. PRC1 and PRC2 catalyze distinct histone modifications, establishing repressive chromatin at shared targets. How PRC1, which consists of canonical PRC1 (cPRC1) and variant PRC1 (vPRC1) complexes, and PRC2 cooperate to silence genes and support mouse embryonic stem cell (mESC) self-renewal is unclear. Using combinatorial genetic perturbations, we show that independent path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 63 publications
5
47
0
Order By: Relevance
“…1A). Consistent with the largely overlapped distributions of H2Aub and H3K27me3 in mESCs (Blackledge et al 2020;Tamburri et al 2020;Zepeda-Martinez et al 2020), H2Aub also exhibited similar genomic distribution to H3K27me3 in oocytes ( Fig. 1A).…”
Section: H2aub Exhibits a Similar Landscape To H3k27me3 With Broad DIsupporting
confidence: 76%
See 1 more Smart Citation
“…1A). Consistent with the largely overlapped distributions of H2Aub and H3K27me3 in mESCs (Blackledge et al 2020;Tamburri et al 2020;Zepeda-Martinez et al 2020), H2Aub also exhibited similar genomic distribution to H3K27me3 in oocytes ( Fig. 1A).…”
Section: H2aub Exhibits a Similar Landscape To H3k27me3 With Broad DIsupporting
confidence: 76%
“…While the classic model suggested recruitment of PRC1 by PRC2-mediated H3K27me3 deposition (Cao et al 2002;Wang et al 2004), recent studies also demonstrated the recruitment of PRC2 by PRC1-mediated H2Aub deposition (Blackledge et al 2014;Blackledge et al 2020;Tamburri et al 2020), suggesting a reciprocal recognition of H2Aub and H3K27me3 by PRC2 and PRC1 respectively. Indeed, PRC1/H2Aub and PRC2/H3K27me3 have been reported to largely overlap in the genome, particularly at canonical PcG targets (i.e., promoters of bivalent genes) (Boyer et al 2006;Ku et al 2008;Blackledge et al 2015;Blackledge et al 2020;Tamburri et al 2020;Zepeda-Martinez et al 2020). However, whether they repress PcG target genes cooperatively or redundantly is still under debate (Blackledge et al 2015;Schuettengruber et al 2017;Cohen et al 2021), and it is largely obscure if they may also function independently at different genomic regions in some biological context.…”
Section: Introductionmentioning
confidence: 99%
“…The PRC1 family includes six distinct subtypes, PRC1. 1-6, which share RING1A or RING1B as a common subunit bearing enzymatic activity for ubiquitination of histone H2A at lysine 119, but differ in their composition of other subunits (5)(6)(7)(8)(9). The PRC1 family is largely classified into two groups, i.e., canonical (PRC1.2 and PRC1.4) and non-canonical (PRC1.1, PRC1.3, PRC1.5, and PRC1.…”
Section: Introductionmentioning
confidence: 99%
“…We detected 1735 peaks with significant RING1B enrichment facilitating identification of cPRC1 and vPRC1 binding sites in SUDHL4 cells ( Figure 7C, D ). Similar to other cell types (Fursova et al, 2019; Scelfo et al, 2019; Zepeda-Martinez et al, 2020), only a fraction of RING1B overlapped with H3K27me3 suggesting that most PRC1 targeting involves PRC2-independent mechanisms (groups 3-10, vPRC1 targets). CBX8 was preferentially enriched at H3K27me3 targets, consistent with its proposed role in cPRC1 recruitment (groups 1 and 2, cPRC1 targets) ( Figure 7D ).…”
Section: Resultsmentioning
confidence: 79%
“…The combinatorial nature of PRC1 assembly and its partial redundancy have hampered functional dissection of canonical and variant PRC1 subunits using classical genetic approaches. Adding to a chemical biology tool kit including small molecule-induced degraders of polycomb group proteins (Dobrinić et al, 2020; Hsu et al, 2020; Ma et al, 2020; Potjewyd et al, 2020; Zepeda-Martinez et al, 2020), UNC7040 provides an opportunity for selective, acute and reversible inactivation of CBX8 reader activity to distinguish its role in canonical PRC1 regulation. The versatility of UNC7040 to examine canonical CBX8 function without laborious genetic manipulations will be very impactful to study its functions in gene regulation of different cell types and tissues, in normal development and disease.…”
Section: Discussionmentioning
confidence: 99%